Predicting (in)correctly: listeners rapidly use unexpected information to revise their predictions. Issue 9 (3rd November 2020) - Chow, Wing-Yee; Chen, Di
ABSTRACT: Comprehenders can incorporate rich contextual information to predict upcoming input on the fly, and cues that conflict with their predictions are quickly detected. The present study examined whether and how comprehenders may revise their existing predictions upon encountering a prediction-inconsistent cue. We took advantage of the rich classifier system in Mandarin Chinese and tracked participants' eye-movements as they listened to sentences in which the final noun is preceded by a classifier which was either compatible with the most expected noun, incompatible with the most expected noun but indicative of another contextually suitable noun, or uninformative. We found that, upon hearing a prediction-inconsistent classifier, listeners quickly directed their eye gaze away from the originally expected object and immediately onto the (initially) unexpected but contextually suitable object. This provides initial evidence that listeners can quickly use prediction-mismatching cues to revise their existing predictions on the fly.